Self-observation as a pedagogical method in the education of people with Autism Spectrum Disorders (ASD) - Avramidi, Athina; Drossinou-Korea Maria (Technium Social Sciences Journal, 2020)
In the present paper, the method of self-observation is examined as the basis for the pedagogy of special educational interventions in people with Autism Spectrum Disorders (ASD) (American Psychiatric Association, 2013). This is part of the informal pedagogical assessment that parents attempt as co-educators but also philologists as intervening educators in order to understand children with autism. The main work case explores the dynamics of pedagogical self-observation in a specific case study from Truffaut’s French film, "The Wild Child" (Itard, 1990). The methodology of observing the special educational needs with emphasis on ADS is applied according to the pedagogical tool, the Targeted Individual Structured Integration Program of Special Education and Training (TISIPSET) (Drossinou-Korea, 2017). The results present data from the interactive relationship during homeschooling between the educator and physician Itard, who has adopted and educates Victor "The Wild Child." The observations and self-observations recorded confirm the difficulties of understanding childhood autism.